Arthrogryposis, renal dysfunction and cholestasis (ARC) syndrome: a rare association with high GGT level and absent kidney. (9th August 2018) - Gupta, Vishal; Pandita, Aakash; Panghal, Astha; Kallem, Venkat
Abstract : We report a case of a term baby presenting with neonatal cholestasis and upper limb flexion deformity on day 4 of life. On further evaluation, high gamma glutamyl transpeptidase (GGT) levels and absent left kidney were found. A diagnosis of arthrogryposis, renal dysfunction and cholestasis (ARC) syndrome was made which is a rare autosomal recessive disorder with primarily clinical diagnosis. Outcome of this condition is dismal. It has a large spectrum of clinical manifestations, but association with high GGT levels and absent kidney is quite rare. No single case report has observed such an association, and this is the first case of ARC syndrome reported from India to the best of our knowledge.